2019
DOI: 10.1111/1440-1681.13065
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine enhances activity thermogenesis and energy expenditure in rats

Abstract: Summary Caffeine and its derivatives have been used, alone and in combination with other phytochemicals, as weight‐loss supplements. Caffeine affects several physiological and behavioural aspects of energy balance, including increasing locomotor activity. This study investigates the potential for caffeine to enhance activity thermogenesis and energy expenditure (EE) even when activity level is held constant. To do this, EE and muscle thermogenesis were measured in rats during treadmill walking regimens, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
1
16
0
1
Order By: Relevance
“…The role of caffeine has also been matter of debate in some cola drinking studies. Caffeine has shown to enhance thermogenesis and energy expenditure in rats [36], but doses used in this paper are far higher than doses we calculated to be provided by cola and light cola drinking [12]. Consistently with other studies, we found that regular cola impaired glucose tolerance and decreased HDL cholesterol [1012,24].…”
Section: Discussionsupporting
confidence: 88%
“…The role of caffeine has also been matter of debate in some cola drinking studies. Caffeine has shown to enhance thermogenesis and energy expenditure in rats [36], but doses used in this paper are far higher than doses we calculated to be provided by cola and light cola drinking [12]. Consistently with other studies, we found that regular cola impaired glucose tolerance and decreased HDL cholesterol [1012,24].…”
Section: Discussionsupporting
confidence: 88%
“…In contrast to WAT, BAT is widely reported as ‘good fat’, increasing thermogenesis and insulin sensitivity. A large body of literature report that caffeine enhances thermogenesis and energy expenditure, leading to fat loss [ 38 ]. Indeed, a study by Velickovic et al demonstrated, both in vitro and in vivo, that an exposure to caffeine significantly increases adipocytes’ thermogenesis and induces browning-like structural changes in mitochondrial and lipid droplet content [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, methylxanthines, such as caffeine and theobromine, have been recognized as effective phytochemicals in weight control, and in the prevention of obesity and type 2 diabetes. Caffeine increases the metabolic rate, energy expenditure, lipid oxidation, and basal-lipolytic and thermogenic activities in the adipose tissue [15,16]. Meanwhile, theobromine has been evidenced as a browning agent that improves lipid catabolic metabolism via the β-adrenergic and AMP-activated protein kinase (AMPK) signaling pathway.…”
Section: Introductionmentioning
confidence: 99%